Fortalecimiento de la gestión cultural de la dirección de desarrollo cantonal del municipio del cantón Pindal desde el principio del autodesarrollo comunitario - Escudero Sánchez, Carlos Leonel (2012)
The process of "STRENGTHENING CULTURAL MANAGEMENT MANAGEMENT DEVELOPMENT OF THE MUNICIPALITY OF CANTON CANTONAL PINDAL SELF FROM THE BEGINNING OF COMMUNITY", was based on a study of the contradictions of the system of relations Cantonal Agency for Development and Population Municipal in the cultural component from a Community Self methodology, which included workshops indifferent. The research was built with the involvement of municipal authorities as well as officials and employees of the Cantonal Development Division, adjusting in five workshops through a reflection of the problems of management, analysis of how to contribute to its growth and strengthening. Work meetings and workshops are the formalized assisted with group dynamics and sharing tools; is reflected towards the future from what has been done by the management and growth on the agreements and commitments made in the multiple social spaces where they build an awareness achieved critical subjects of municipal government to encourage the role of the population. He spoke of challenges, opportunities and solutions to make social arrangements for the emancipation of the people observed from each attendee to explain best possible personal and community involvement, the need to break with the traditional management direction about cultural projects, thus scheduled activities with those committed to this challenge. Identifying the need for dialogue, communication and community action among them, took part to the foundation of an alternative model of cultural work - community to promote the deployment of cultural projects, our research experience has been consistent with these concepts, which have left Learning on the need to continue growing to overcome personal obstacles, and institutional group.